Die profile design for tube extrusion and its experimental verification - Pathak,K. K. (2010)
In this study, experimental verification of a proposed extrusion die profile design approach, which aims to satisfy microstructural criteria at maximum production speed and minimum left out material in the die cavity, is presented. The design problem is formulated as a nonlinear programming problem, which is solved using genetic algorithm (GA). Selection of the processing parameters is carried out using dynamic material modeling (DMM). Microstructural study reveals considerable grain refinement in the extruded tube.